Pengetahuan, sikap, motivasi ibu, dan praktik pemberian MP-ASI pada anak usia 6-23 bulan: studi formatif di Aceh - Aripin Ahmad; Siti Madanijah; Cesilia Meti Dwiriani; Risatianti Kolopaking (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2019)
Maternal knowledge, attitude, motivation and complementary feeding practice of children aged 6-23 months: formative study in AcehBackground: Poor knowledge, attitude, and motivation of the mother determine complementary feeding (CF) practice of the child resulting in poor nutrition fulfillment. Objective: This study aimed to analyze maternal knowledge, attitude, motivation, and relationships with the CF practice of children aged 6-23 months.Method: A cross-sectional study and cluster random sampling was applied to select 392 mothers of children aged 6-23 months in Aceh Besar District. Data on maternal knowledge, attitude, and motivation were collected using valid and reliable structured questionnaire. CF practice quality was assessed using indicators of timely introduction to CF, minimum meal frequency, minimum dietary diversity, and minimum acceptable diet according to WHO recommendation. The association of maternal knowledge, attitude, and motivation with CF practice was analyzed using binary logistic regression with a 95% confidence level (α=0.05).Results: There was a small proportion of mothers (20.2%, 8.7%, 33.9%) having good knowledge, attitude, and motivation, respectively. Overall, there was one-fourth (23%) of the children aged 6-23 months receiving CF as recommended by WHO. There were significant correlations between maternal knowledge and attitude (r=0.606, p<0.01) and motivation (r=0.103, p<0.05). Education level and motivation were the risk factors of improper CF practice (OR=4.25; 95% CI: 1.10-16.36; p=0.035and OR=1.83; 95% CI: 1.05-3.16; p=0.031, respectively). Conclusion: Maternal knowledge, attitude, and motivation of children aged 6-23 months in Aceh were still poor, shown by improper CF practice. Therefore, an effort to improve nutrition education, particularly by health personnel and stakeholder, to be specific and targeted is important.